PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN BARANG BEKAS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PENDIDIKAN GURU SEKOLAH DASAR - Ruqoyyah, Siti; Arga, Hana Sakura Putu; Kelana, Jajang Bayu; Altaftazani, Deden Herdiana (IKIP Siliwangi Bandung, 2020)
This research is motivated by the low students' mathematical communication skills. The purpose of this research is to see the achievement and improvement of the mathematical communication skills of students who get learning using a project-based learning model assisted by used goods using conventional learning. This study used a quasi-experimental method with a non-equivalent pretest and posttest control group design. The subjects of this study were 70 students of the second-semester elementary school teacher candidates at IKIP Siliwangi. The instrument in this study used a test. The results showed that 1) the achievement of mathematical communication skills of students who received learning using a project-based learning model assisted with used goods was better than those who used conventional learning; 2) the improvement of students' mathematical communication skills who get learning using a project-based learning model with used goods is better than those who use conventional learning.